THE EFFECT OF LASER-ASSISTED HATCHING ON PREGNANCY OUTCOMES OF VITRIFICATION FROZEN EMBRYO TRANSFER - Vellyana Lie; Andri Rezano; Tono Djuwantono; Maitra Djiang Wen (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights LAH might effectively increase pregnancy outcomes for frozen-thawed embryo transfer. Zona pellucida drilling might help increase pregnancy outcomes in FET. Abstract Background: Zona Pellucida (ZP) thickness of less than 16 mm is better for embryo implantation inside the endometrium. Laser Assisted Hatching (LAH) is commonly used, especially in non-contact mode, using a 1.48-um infrared diode laser beam because of its short exposure time, accurate positioning, simple operation, indirect contact, safety, and effectiveness. Objective: This paper describes the potential of laser-assisted hatching in biochemical pregnancy outcomes in Frozen Embryo Thawed transfers. Material and Method: The total number of patients enrolled in this study was 141. Patients were prospectively treated during embryo transfers at Pusat Fertilitas Bocah Indonesia, Primaya Hospital at Tangerang, Indonesia, from December 2020 until December 2021. Result: There were no significant differences between the LAH and no-LAH groups regarding average age, infertility duration, infertility type, and etiology of infertility (p>0.05). In the same line, the blastocyst (0.76 ± 0.87; 1.25 ± 1.08) compared with cleavage (0.72 ± 0.84; 0.67 ± 0.98) (p<0.534 and p< .032). There was no significant difference, even though clinically, the proportions of live births, multiple pregnancies, biochemical pregnancies, and ongoing pregnancies in the LAH group were not exceptions to the outcomes of failures and miscarriages. Conclusion: LAH did not appear to increase the pregnancy rate in this study. However, the methodology seems to reduce bias in this study by considering methodology for selecting FET embryos based on the cryopreserved condition, embryo quality, and precise LAH.